The complex ATP–Fe(2+) serves as a specific affinity cleavage reagent in ATP-Mg(2+) sites of Na,K-ATPase: Altered ligation of Fe(2+) (Mg(2+)) ions accompanies the E(1)P→E(2)P conformational change - Patchornik, Guy (The National Academy of Sciences, 2000)
In the presence of ascorbate/H(2)O(2), ATP–Fe(2+) or AMP-PNP–Fe(2+) complexes act as affinity cleavage reagents, mediating selective cleavage of the alpha subunit of Na,K-ATPase at high affinity ATP–Mg(2+) sites. The cleavages reveal contact points of Fe(2+) or Mg(2+) ions. In E(1) and E(1)Na conformations, two major cleavages are detected within the conserved (708)TGDGVNDSPALKK sequence (at V712 and nearby), and one (E(1)Na) or two (E(1)) minor cleavages near V440. In media containing sodium and ATP, Fe(2+) substitutes for Mg(2+) in activating phosphorylation and ATP hydrolysis. In the E(1)P conformation, cleavages are the same as in E(1). Fe(2+) is not bound tightly. By contrast, in the E(2)P conformation, the pattern is different. A major cleavage occurs near the conserved sequence (212)TGES, whereas those in TGDGVNDSPALKK are less prominent. Fe(2+) is bound very tightly. On E(2)P hydrolysis, the Fe(2+) dissociates. The results are consistent with E(1)↔E(2) conformation-dependent movements of cytoplasmic domains and sites for P(i) and Mg(2+) ions, inferred from previous Fe-cleavage experiments. Furthermore, these concepts fit well with the crystal structure of Ca-ATPase [Toyoshima, C., Nakasako, M., Nomura, H. & Ogawa, H. (2000) Nature (London) 405, 647–655]. Altered ligation of Mg(2+) ions in E(2)P may be crucial in facilitating nucleophilic attack of water on the O—P bond. Mg(2+) ions may play a similar role in all P-type pumps. As affinity cleavage reagents, ATP–Fe(2+) or other nucleotide–Fe(2+) complexes could be widely used to investigate nucleotide binding proteins.